(3aJhM CQV QHjYI hOjGQ HcQ hGdLRjQI hGdYQGbs - (3eMeO Hf YeQ Hf hGbO GdSgej GdCSdej HGdhdGA, GdeOfj, CHh YHO Gddg, GdhGbOj,J (B207 (3g` s
(3ChdgG (B:s
(3MOKfG jhfS YHO GdCYdi bQGAI Ydjg s
(3BNQgG (B:s
(3gPG eGcGf ef aJhM OjGQ HcQ hOjGQ eVQ hHdGO QHjYI Ydi GdJeGe s
(3hjYJHQ gPG GdcJGH LRA ef (B"(3aJhM GdYLe hGdYQGb(B" (3GdPi PcQg HQhcdeGf edMb(B1/208s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B311 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B95s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B208 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B195 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(2896) s
Keywords: (3GdJGQjNs